The effects of shark liver oil on fibroblasts and collagen density in the periodontal ligaments of Wistar rats induced with Porphyromonas gingivalis - Dian Mulawarmanti; Dwi Andriani; Dian Widya Damaiyanti; Farizia Putri Khoirunnisa; Alifati Nita Juliatin (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Periodontitis is an infection in tooth-supporting tissues caused by a specific microorganism, Porphyromonas Gingivalis (PG), which can trigger collagen destruction. Generally, periodontal therapy employs a combination of mechanical (scaling root planning/SRP) and chemical (antibiotics) remedies, the latter of which can cause bacterial resistance. On the other hand, shark liver oil contains active natural ingredients such as alkylglycerols, squalene, squalamine, and omega-3, which have antibacterial and antioxidant effects. Purpose: This study aims to determine the impact of shark liver oil on fibroblasts and collagen density in the periodontal ligament of Wistar rats induced with PG. Methods: This study represents a laboratory experiment with post-test only control group design. The research subjects consisted of 35 Wistar rats divided into five groups, namely; a negative control group (K-); a positive control group with PG induction (K+); and three treatment groups induced with PG and shark liver oil once a day for seven days at varying doses of 0.2 g/gBB (P1), 0.3 g/gBB (P2), and 0.4 g/gBB (P3). Following treatment, the subjects were euthanized. The number of fibroblasts was then histologically examined with Hematoxylin Eosin (HE). Meanwhile, the collagen density was histologically analyzed with Masson’s Tricrome. Fibroblast cells were observed through a microscope at 400x magnification. Data was statistically analyzed with a one-way ANOVA and post hoc LSD. Collagen Density scoring was then performed. The results were analyzed with a non-parametric Kruskal-Wallis test (p=0.05), and subsequently with a Mann-Whitney U test (p<0.05). Results: The number of fibroblasts in the periodontal ligament areas of each group were 18.6 ± 1.21 for K-; 12 ± 1.26 for K;16.8 ± 1.72 for P1; 17.1 ± 1.94 for P2; and 23.16 ± 2.78 for P3. The results also indicated that there were significant differences between K- with K+ and P3, K+ with P1, P2, and P3, as well as P3 with P1 and P2. However, there was no significant difference between K- and P1 and P2 or P1 and P2. The results showed that collagen density in the negative control group did not significantly decrease compared to that in the positive control group in which PG was induced. Meanwhile, collagen density in all three treatment groups following doses of 0.2 g/gBB, 0.3 g/gBB, and 0.4 g/gBB being administered significantly increased compared to that in the negative control group and the positive control group subjected to PG induction. Conclusion: Shark liver oil can significantly increase fibroblast cells and collagen density in the periodontal ligament of Wistar rats induced with PG.